High-strength PET (Polyethylene Terephthalate) composite copper foil electroplating solution and surface copper electroplating process
By using specific additives and processes to prepare high-strength PET composite copper foil electroplating solution, the problems of insufficient safety of traditional copper foil and unclear additives are solved, and the production of copper foil with high strength and low roughness is achieved, reducing production costs.
Patent Information
- Application Number
- CN202410182845.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-19
- Publication Date
- 2025-08-19
AI Technical Summary
In existing lithium-ion batteries, traditional pure copper foils are insufficient in safety, and the electroplating solution additive formula of composite copper foil depends on import and is unclear, resulting in high production costs and easy deactivation of additives, affecting the strength and surface quality of the copper foil.
Additives such as polyethylene glycol, hydroxyethyl cellulose, 1-(3-propylamine)-3-butylimidazole tetrafluoroborate, methylthiothiadiazole, etc. are prepared by combining plasma coarsing and two-step magnetron sputtering process to prepare high-strength PET composite copper foil plating solution, and control the plating parameters to improve the strength and surface quality of the copper foil.
It has achieved the increase in tensile strength and elongation of high-strength PET composite copper foil, reduced surface roughness, reduced production costs, and is suitable for industrial production.
Smart Images

Figure CN120505676A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, in particular to a high-strength PET composite copper foil electroplating solution and a surface copper electroplating process. Background Art
[0002] The rapid growth of the new energy vehicle industry has further driven the development of the lithium-ion battery sector. Copper foil, as the fundamental material for the negative electrode current collector in lithium-ion batteries, has a significant impact on the performance and lifespan of lithium-ion batteries. Traditional negative electrode current collectors are typically made of high-purity copper foil. However, pure copper foil has a serious drawback in lithium-ion battery use, namely, insufficient safety. Fires in new energy electric vehicles following accidents are caused by copper foil ruptures that puncture the separator, resulting in a short circuit between the positive and negative electrodes. Numerous solutions have been proposed across various industries to address lithium-ion battery safety issues. Among these solutions, composite current collectors have emerged as the most effective, replacing traditional pure metal copper foil with composite copper foil. Composite copper foil has a completely different structural structure from pure metal copper foil, consisting of a copper foil layer, a polymer film layer, and a copper foil layer. This unique structure makes it exceptionally safe. In the event of a rupture or puncture in the composite copper foil, the polymer film layer effectively interrupts the circuit, preventing battery explosions.
[0003] In the preparation of composite copper foil, water electroplating process parameters and additives will greatly affect the quality of composite copper foil. Among them, the additive formula is the most important factor in controlling the surface quality and mechanical properties of composite copper foil. The appropriate electroplating solution formula can make the composite copper foil obtain better quality.
[0004] However, most domestic companies currently rely heavily on imports for their water electroplating additive formulas. The effects and dosages of the additives are unclear, and there are many types of electroplating solution additives. The lack of clarity in the plating solution formula not only increases the company's production costs, but also restricts them to long-term foreign technology constraints. Furthermore, existing traditional additives are often used empirically without considering their shortcomings and deficiencies. For example, while gelatin can be an excellent additive to improve the performance of copper foil, it has a time-limited nature and will become inactivated after prolonged exposure to acidic conditions, requiring activated carbon adsorption for removal. Furthermore, chloride ions in the plating solution can also accelerate the inactivation of gelatin. Therefore, designing and developing a limited but superior electroplating solution additive formula is of great and far-reaching significance for the production of high-end composite copper foil. Summary of the Invention
[0005] The object of the present invention is to provide a high-strength PET composite copper foil electroplating solution and a surface copper electroplating process to solve the problems raised in the above background technology.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: a high-strength PET composite copper foil electroplating solution and a surface copper electroplating process, comprising the following steps:
[0007] Step 1:
[0008] Clean the surface of the PET film and set aside;
[0009] Step 2:
[0010] The cleaned and dried PET film was subjected to plasma roughening treatment in an air atmosphere;
[0011] Step 3:
[0012] A two-step magnetron sputtering process was used to coat a layer of copper film on both sides of the roughened PET film to obtain a PET base film.
[0013] Step 4:
[0014] preparing a mixed electrolyte of copper sulfate and sulfuric acid using deionized water to obtain a basic electrolyte;
[0015] Step 5:
[0016] Adding the basic electrolyte and the additive into the electrolytic tank at the same time, stirring continuously to uniformly mix the additive into the basic electrolyte, to obtain an electroplating solution;
[0017] Step 6:
[0018] The PET base film in step 3 is used as the cathode and the ruthenium-iridium-titanium mesh is used as the anode. The temperature of the electroplating solution is controlled to perform copper electroplating to obtain a PET composite copper foil. After the electroplating is completed, the PET composite copper foil is taken out and the surface plating solution is rinsed with deionized water and then dried with cold air.
[0019] Furthermore, in step 1, the surface of the PET film is cleaned by placing the PET film in acetone and ethanol solutions in sequence for ultrasonic cleaning for 10 to 15 minutes, then washing with deionized water and drying.
[0020] Furthermore, in step 2, the plasma roughening process is as follows: the polymer film is placed on the plasma generator tray, the air is passed into the reaction chamber after passing through the drying tower, and the air pressure is evacuated to 50-60 Pa. After the air flow stabilizes, microwave discharge is performed, the discharge power is controlled to 80-100 W, and the reaction time is 40-60 s.
[0021] Furthermore, in step 3, the two-step magnetron sputtering process is as follows: the first step is to sputter a 10-15 nm copper film on both sides of the PET film, and the second step is to adjust the magnetron sputtering parameters and continue to sputter a copper film with a thickness of 10-25 nm, and finally sputter a 25-40 nm copper film on both sides of the PET film.
[0022] Furthermore, in step 4, in the basic electrolyte, the copper ion concentration of the basic electrolyte is 80-100 g / L, and the sulfuric acid concentration is 100-120 g / L.
[0023] Furthermore, in step 5, the additive consists of an organic additive and an inorganic additive containing chloride ions.
[0024] Furthermore, in step 5, the organic additive is at least one of polyethylene glycol (PEG), hydroxyethyl cellulose (HEC), 1-(3-propylamino)-3-butylimidazolium tetrafluoroborate ([NH2p-BIM]BF4), and methylmercaptothiadiazole ([P8][MMT]).
[0025] Furthermore, in step 5, the inorganic additive containing chloride ions is at least one of hydrochloric acid and sodium chloride.
[0026] Furthermore, in step 5, in the plating solution, the concentration of polyethylene glycol is 0-2 mg / L; the concentration of hydroxyethyl cellulose is 0-6 mg / L; the concentration of 1-(3-propylamino)-3-butylimidazole tetrafluoroborate is 0-5 mg / L; the concentration of methylmercaptothiadiazole is 0-3 mg / L; and the concentration of chloride ions is 0-5 mg / L.
[0027] Furthermore, in step 6, the temperature of the electroplating solution is controlled at 40-60°C.
[0028] Furthermore, in step 6, the current density of the electrodeposition is 1 to 5 A / dm 2 .
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] Existing electroplating solution additive formulas rely on imports, with a wide variety of formulas and unclear mechanisms of action of each additive. Moreover, the additive system suffers from decomposition and inactivation during the PET copper foil water electroplating process, requiring frequent removal and replacement of additives. This not only greatly increases manpower and material costs, but also makes it difficult to accurately control the concentration of additives in the plating solution.
[0031] The high-strength PET composite copper foil electroplating solution provided by the present invention offers a limited number of formulations and high stability. The water electroplating process effectively increases the tensile strength of the PET composite copper foil and reduces its surface roughness, overcoming the lower strength of copper foil produced using existing techniques. Frequent replacement of the electroplating solution is also unnecessary. The PET composite copper foil produced using the present invention achieves room-temperature tensile strength and elongation as high as 341.2 MPa and 29.3%, respectively, with a roughness as low as 3.132 μm. This approach is conducive to large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:
[0033] Figure 1 This is a surface microscopic morphology of the PET composite copper foil prepared in Example 4 of the present invention;
[0034] Figure 2 This is a surface microscopic morphology of the PET composite copper foil prepared in Example 6 of the present invention;
[0035] Figure 3 This is a surface microscopic morphology of the PET composite copper foil prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0036] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0037] It should be noted that there are no special restrictions on the purchase manufacturers of all raw materials involved in the present invention, which include, for example: PET film from Toray Industries, Ltd., with a specification of 4.5 μm; ruthenium iridium titanium mesh from Suzhou Shultai Industrial Technology Co., Ltd.; polyethylene glycol (8000-10000) from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0038] Example 1: A high-strength PET composite copper foil electroplating solution and surface copper electroplating process, comprising the following steps:
[0039] Step 1: Place the PET film in acetone and ethanol solutions for ultrasonic cleaning for 10 minutes, then rinse with deionized water and blow dry at room temperature for later use;
[0040] Step 2: The cleaned and dried PET film is subjected to plasma roughening treatment in an air atmosphere. The plasma roughening process is as follows: the polymer film is placed on a plasma generator tray, air is passed through a drying tower and then introduced into the reaction chamber, which is evacuated to a pressure of 60 Pa. After the airflow stabilizes, microwave discharge is performed, with the discharge power controlled at 100 W and the reaction time at 60 s.
[0041] Step 3: A two-step magnetron sputtering process is used to deposit a layer of copper film on both sides of the roughened PET film. In the first step, a 15nm copper film is sputtered on the surface of the PET film. In the second step, after adjusting the magnetron sputtering parameters, a 10nm thick copper film is sputtered. Finally, a 25nm copper film is sputtered on both sides of the PET film to obtain a PET base film.
[0042] Step 4: Using deionized water, prepare a mixed electrolyte of copper sulfate and sulfuric acid to obtain a basic electrolyte; wherein the copper ion concentration is 80 g / L and the sulfuric acid concentration is 100 g / L;
[0043] Step 5: Adding the base electrolyte and the additive to the electrolytic cell simultaneously, and continuously stirring to uniformly mix the additive in the base electrolyte to obtain an electroplating solution; wherein the concentration of 1-(3-propylamino)-3-butylimidazole tetrafluoroborate is 10 mg / L, and the concentration of hydrochloric acid is 5 mg / L;
[0044] Step 6: Use the PET base film in step 3 as the cathode and the ruthenium-iridium-titanium mesh as the anode. Control the plating solution temperature to 50°C and the current density to 4A / dm 2 Electroplating copper was performed, and after the electroplating was completed, the PET composite copper foil was taken out, the surface plating solution was rinsed with deionized water, and then dried with cold air at room temperature.
[0045] Example 2: A high-strength PET composite copper foil electroplating solution and surface copper electroplating process, comprising the following steps:
[0046] Step 1: Place the PET film in acetone and ethanol solutions for ultrasonic cleaning for 10 minutes, then rinse with deionized water and blow dry at room temperature for later use;
[0047] Step 2: The cleaned and dried PET film is subjected to plasma roughening treatment in an air atmosphere. The plasma roughening process is as follows: the polymer film is placed on a plasma generator tray, air is passed through a drying tower and then introduced into the reaction chamber, which is evacuated to a pressure of 60 Pa. After the airflow stabilizes, microwave discharge is performed, with the discharge power controlled at 100 W and the reaction time at 60 s.
[0048] Step 3: A two-step magnetron sputtering process is used to deposit a layer of copper film on both sides of the roughened PET film. In the first step, a 15nm copper film is sputtered on the surface of the PET film. In the second step, after adjusting the magnetron sputtering parameters, a 10nm thick copper film is sputtered. Finally, a 25nm copper film is sputtered on both sides of the PET film to obtain a PET base film.
[0049] Step 4: Using deionized water, prepare a mixed electrolyte of copper sulfate and sulfuric acid to obtain a basic electrolyte; wherein the copper ion concentration is 80 g / L and the sulfuric acid concentration is 100 g / L;
[0050] Step 5: Adding the base electrolyte and the additive to the electrolytic cell simultaneously, and continuously stirring to uniformly mix the additive in the base electrolyte to obtain an electroplating solution; wherein the concentration of 1-(3-propylamino)-3-butylimidazole tetrafluoroborate is 10 mg / L, the concentration of methylthiothiadiazole is 3 mg / L, and the concentration of hydrochloric acid is 5 mg / L;
[0051] Step 6: Use the PET base film in step 3 as the cathode and the ruthenium-iridium-titanium mesh as the anode. Control the plating solution temperature to 50°C and the current density to 4A / dm 2 Electroplating copper was performed, and after the electroplating was completed, the PET composite copper foil was taken out, the surface plating solution was rinsed with deionized water, and then dried with cold air at room temperature.
[0052] Example 3: A high-strength PET composite copper foil electroplating solution and surface copper electroplating process, comprising the following steps:
[0053] Step 1: Place the PET film in acetone and ethanol solutions for ultrasonic cleaning for 10 minutes, then rinse with deionized water and blow dry at room temperature for later use;
[0054] Step 2: The cleaned and dried PET film is subjected to plasma roughening treatment in an air atmosphere. The plasma roughening process is as follows: the polymer film is placed on a plasma generator tray, air is passed through a drying tower and then introduced into the reaction chamber, which is evacuated to a pressure of 60 Pa. After the airflow stabilizes, microwave discharge is performed, with the discharge power controlled at 100 W and the reaction time at 60 s.
[0055] Step 3: A two-step magnetron sputtering process is used to deposit a layer of copper film on both sides of the roughened PET film. In the first step, a 15nm copper film is sputtered on the surface of the PET film. In the second step, after adjusting the magnetron sputtering parameters, a 10nm thick copper film is sputtered. Finally, a 25nm copper film is sputtered on both sides of the PET film to obtain a PET base film.
[0056] Step 4: Using deionized water, prepare a mixed electrolyte of copper sulfate and sulfuric acid to obtain a basic electrolyte; wherein the copper ion concentration is 80 g / L and the sulfuric acid concentration is 100 g / L;
[0057] Step 5: Adding the base electrolyte and the additives to the electrolytic cell simultaneously, and continuously stirring to uniformly mix the additives in the base electrolyte to obtain an electroplating solution; wherein the concentration of 1-(3-propylamino)-3-butylimidazole tetrafluoroborate is 10 mg / L, the concentration of methylmercaptothiadiazole is 3 mg / L, the concentration of polyethylene glycol is 2 mg / L, and the concentration of hydrochloric acid is 5 mg / L;
[0058] Step 6: Use the PET base film in step 3 as the cathode and the ruthenium-iridium-titanium mesh as the anode. Control the plating solution temperature to 50°C and the current density to 4A / dm 2Electroplating copper was performed, and after the electroplating was completed, the PET composite copper foil was taken out, the surface plating solution was rinsed with deionized water, and then dried with cold air at room temperature.
[0059] Example 4: A high-strength PET composite copper foil electroplating solution and surface copper electroplating process, comprising the following steps:
[0060] Step 1: Place the PET film in acetone and ethanol solutions for ultrasonic cleaning for 10 minutes, then rinse with deionized water and blow dry at room temperature for later use;
[0061] Step 2: The cleaned and dried PET film is subjected to plasma roughening treatment in an air atmosphere. The plasma roughening process is as follows: the polymer film is placed on a plasma generator tray, air is passed through a drying tower and then introduced into the reaction chamber, which is evacuated to a pressure of 60 Pa. After the airflow stabilizes, microwave discharge is performed, with the discharge power controlled at 100 W and the reaction time at 60 s.
[0062] Step 3: A two-step magnetron sputtering process is used to deposit a layer of copper film on both sides of the roughened PET film. In the first step, a 15nm copper film is sputtered on the surface of the PET film. In the second step, after adjusting the magnetron sputtering parameters, a 10nm thick copper film is sputtered. Finally, a 25nm copper film is sputtered on both sides of the PET film to obtain a PET base film.
[0063] Step 4: Using deionized water, prepare a mixed electrolyte of copper sulfate and sulfuric acid to obtain a basic electrolyte; wherein the copper ion concentration is 80 g / L and the sulfuric acid concentration is 100 g / L;
[0064] Step 5: Adding the base electrolyte and the additives to the electrolytic cell simultaneously, and continuously stirring to uniformly mix the additives in the base electrolyte to obtain an electroplating solution; wherein the concentration of 1-(3-propylamino)-3-butylimidazole tetrafluoroborate is 10 mg / L, the concentration of methylmercaptothiadiazole is 3 mg / L, the concentration of polyethylene glycol is 2 mg / L, the concentration of hydroxyethyl cellulose is 6 mg / L, and the concentration of hydrochloric acid is 5 mg / L;
[0065] Step 6: Use the PET base film in step 3 as the cathode and the ruthenium-iridium-titanium mesh as the anode. Control the plating solution temperature to 50°C and the current density to 4A / dm 2 Electroplating copper was performed, and after the electroplating was completed, the PET composite copper foil was taken out, the surface plating solution was rinsed with deionized water, and then dried with cold air at room temperature.
[0066] Example 5: A high-strength PET composite copper foil electroplating solution and surface copper electroplating process, comprising the following steps:
[0067] Step 1: Place the PET film in acetone and ethanol solutions for ultrasonic cleaning for 10 minutes, then rinse with deionized water and blow dry at room temperature for later use;
[0068] Step 2: The cleaned and dried PET film is subjected to plasma roughening treatment in an air atmosphere. The plasma roughening process is as follows: the polymer film is placed on a plasma generator tray, air is passed through a drying tower and then introduced into the reaction chamber, which is evacuated to a pressure of 60 Pa. After the airflow stabilizes, microwave discharge is performed, with the discharge power controlled at 100 W and the reaction time at 60 s.
[0069] Step 3: A two-step magnetron sputtering process is used to deposit a layer of copper film on both sides of the roughened PET film. In the first step, a 15nm copper film is sputtered on the surface of the PET film. In the second step, after adjusting the magnetron sputtering parameters, a 10nm thick copper film is sputtered. Finally, a 25nm copper film is sputtered on both sides of the PET film to obtain a PET base film.
[0070] Step 4: Using deionized water, prepare a mixed electrolyte of copper sulfate and sulfuric acid to obtain a basic electrolyte; wherein the copper ion concentration is 80 g / L and the sulfuric acid concentration is 100 g / L;
[0071] Step 5: Adding the base electrolyte and the additives to the electrolytic cell simultaneously, and continuously stirring to uniformly mix the additives in the base electrolyte to obtain an electroplating solution; wherein the concentration of 1-(3-propylamino)-3-butylimidazole tetrafluoroborate is 10 mg / L, the concentration of methylmercaptothiadiazole is 3 mg / L, the concentration of polyethylene glycol is 2 mg / L, the concentration of hydroxyethyl cellulose is 6 mg / L, and the concentration of sodium chloride is 5 mg / L;
[0072] Step 6: Use the PET base film in step 3 as the cathode and the ruthenium-iridium-titanium mesh as the anode. Control the plating solution temperature to 50°C and the current density to 4A / dm 2 Electroplating copper was performed, and after the electroplating was completed, the PET composite copper foil was taken out, the surface plating solution was rinsed with deionized water, and then dried with cold air at room temperature.
[0073] Example 6: A high-strength PET composite copper foil electroplating solution and surface copper electroplating process, comprising the following steps:
[0074] Step 1: Place the PET film in acetone and ethanol solutions for ultrasonic cleaning for 10 minutes, then rinse with deionized water and blow dry at room temperature for later use;
[0075] Step 2: The cleaned and dried PET film is subjected to plasma roughening treatment in an air atmosphere. The plasma roughening process is as follows: the polymer film is placed on a plasma generator tray, air is passed through a drying tower and then introduced into the reaction chamber, which is evacuated to a pressure of 60 Pa. After the airflow stabilizes, microwave discharge is performed, with the discharge power controlled at 100 W and the reaction time at 60 s.
[0076] Step 3: A two-step magnetron sputtering process is used to deposit a layer of copper film on both sides of the roughened PET film. In the first step, a 15nm copper film is sputtered on the surface of the PET film. In the second step, after adjusting the magnetron sputtering parameters, a 10nm thick copper film is sputtered. Finally, a 25nm copper film is sputtered on both sides of the PET film to obtain a PET base film.
[0077] Step 4: Using deionized water, prepare a mixed electrolyte of copper sulfate and sulfuric acid to obtain a basic electrolyte; wherein the copper ion concentration is 80 g / L and the sulfuric acid concentration is 100 g / L;
[0078] Step 5: Adding the base electrolyte and the additives to the electrolytic cell simultaneously, and continuously stirring to uniformly mix the additives in the base electrolyte to obtain an electroplating solution; wherein the concentration of 1-(3-propylamino)-3-butylimidazole tetrafluoroborate is 30 mg / L, the concentration of methylmercaptothiadiazole is 3 mg / L, the concentration of polyethylene glycol is 2 mg / L, the concentration of hydroxyethyl cellulose is 6 mg / L, and the concentration of hydrochloric acid is 5 mg / L;
[0079] Step 6: Use the PET base film in step 3 as the cathode and the ruthenium-iridium-titanium mesh as the anode. Control the plating solution temperature to 50°C and the current density to 4A / dm 2 Electroplating copper was performed, and after the electroplating was completed, the PET composite copper foil was taken out, the surface plating solution was rinsed with deionized water, and then dried with cold air at room temperature.
[0080] Comparative Example 1:
[0081] Step 1: Place the PET film in acetone and ethanol solutions for ultrasonic cleaning for 10 minutes, then rinse with deionized water and blow dry at room temperature for later use;
[0082] Step 2: The cleaned and dried PET film is subjected to plasma roughening treatment in an air atmosphere. The plasma roughening process is as follows: the polymer film is placed on a plasma generator tray, air is passed through a drying tower and then introduced into the reaction chamber, which is evacuated to a pressure of 60 Pa. After the airflow stabilizes, microwave discharge is performed, with the discharge power controlled at 100 W and the reaction time at 60 s.
[0083] Step 3: A two-step magnetron sputtering process is used to deposit a layer of copper film on both sides of the roughened PET film. In the first step, a 15nm copper film is sputtered on the surface of the PET film. In the second step, after adjusting the magnetron sputtering parameters, a 10nm thick copper film is sputtered. Finally, a 25nm copper film is sputtered on both sides of the PET film to obtain a PET base film.
[0084] Step 4: preparing a mixed electrolyte of copper sulfate and sulfuric acid with deionized water to obtain an electroplating solution; wherein the copper ion concentration is 80 g / L and the sulfuric acid concentration is 100 g / L;
[0085] Step 5: Use the PET base film in step 3 as the cathode and the ruthenium-iridium-titanium mesh as the anode. Control the plating solution temperature to 50°C and the current density to 4A / dm 2 Electroplating copper was performed, and after the electroplating was completed, the PET composite copper foil was taken out, the surface plating solution was rinsed with deionized water, and then dried with cold air at room temperature.
[0086] Experiment: Examples 1 to 6 and Comparative Example 1 were tested, and the results are shown in the following table.
[0087] Tensile strength and elongation at break: The test refers to the national standard GB / T 1040.3-2006. The test results of the present invention are all test data in the MD direction;
[0088] Roughness test: Use a roughness tester to scan or contact the copper foil surface using a mechanical probe or other methods.
[0089]
[0090]
[0091] Conclusion: The data of Examples 1 to 6 and Comparative Example 1 show that the PET composite copper foil prepared by the additive in the electroplating solution provided by the present invention has good mechanical properties and can reduce the surface roughness of the PET composite copper foil.
[0092] It should be noted that, in this document, relational terms such as first and second, etc., are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "comprises," "comprising," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a list of elements includes not only those elements but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus.
[0093] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art will be able to modify the technical solutions described in the aforementioned embodiments or substitute equivalents for some of the technical features. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention shall be included within the scope of protection of the present invention.
Claims
1. An electroplating solution additive, characterized in that: The electroplating solution additives include organic additives and inorganic additives containing chloride ions.
2. An electroplating solution additive, characterized in that: The electroplating solution additive meets at least one of the following conditions: (1) The organic additive is at least one of polyethylene glycol, hydroxyethyl cellulose, 1-(3-propylamino)-3-butylimidazole tetrafluoroborate, and methylmercaptothiadiazole; (2) The inorganic additive containing chloride ions is at least one of hydrochloric acid and sodium chloride.
3. A high-strength PET composite copper foil electroplating solution, characterized by: The high-strength PET composite copper foil electroplating solution is prepared by mixing a basic electrolyte and the additive according to claim 1 or 2.
4. The high-strength PET composite copper foil electroplating solution according to claim 3, characterized in that: The base electrolyte is a mixture of deionized water, copper sulfate, and sulfuric acid.
5. The high-strength PET composite copper foil electroplating solution according to claim 4, characterized in that: In the high-strength PET composite copper foil electroplating solution, the copper ion concentration is 60-100 g / L, the sulfuric acid concentration is 80-120 g / L, the polyethylene glycol concentration is 0-2 mg / L; the hydroxyethyl cellulose concentration is 0-6 mg / L; the 1-(3-propylamino)-3-butylimidazole tetrafluoroborate concentration is 0-5 mg / L; the methylmercaptothiadiazole concentration is 0-3 mg / L; and the chloride ion concentration is 0-5 mg / L.
6. Use of the electroplating solution according to claim 4 in a copper electroplating process on a PET film surface, characterized in that: The surface electroplating process includes the following steps: Step 1: Clean and dry the surface of the PET film; Step 2: Plasma roughening treatment of PET film; Step 3: A two-step magnetron sputtering process was used to coat copper films with a composite layer structure on both sides of the roughened PET film to obtain a PET base film. Step 4: The PET base film in step 3 is used as the cathode and the ruthenium-iridium-titanium mesh is used as the anode. Electroplating copper is performed by controlling the temperature of the electroplating solution to obtain a PET composite copper foil. After the electroplating is completed, the PET composite copper foil is taken out, the surface plating solution is washed, and then dried to obtain a high-strength PET composite copper foil.
7. The use according to claim 6, characterized in that: In step 1, the surface cleaning method of the PET film is as follows: the PET film is placed in acetone and ethanol solutions for ultrasonic cleaning for 10 to 15 minutes, and then washed with deionized water and blown dry.
8. The use according to claim 6, characterized in that: In step 2, the plasma roughening process is as follows: the polymer film is placed on the plasma generator tray, the air is passed through the drying tower into the reaction chamber, and the air pressure is evacuated to 50-60 Pa. After the air flow stabilizes, microwave discharge is performed, the discharge power is controlled to 80-100 W, and the reaction time is 40-60 s.
9. The use according to claim 6, characterized in that: In step 3, the two-step magnetron sputtering process is as follows: the first step is to sputter a 10-15 nm copper film on both sides of the PET film; the second step is to continue sputtering a copper film with a thickness of 10-25 nm, and finally form a 25-40 nm copper film on both sides of the PET film.
10. The use according to claim 6, characterized in that: In step 4, the plating solution temperature is 40-60°C, and the current density of the electrodeposition is 1-5A / dm 2 .
